Barriers and facilitators to COVID-19 vaccine acceptability among people incarcerated in Canadian federal prisons: A qualitative study. (April 2022) - Lessard, David; Ortiz-Paredes, David; Park, Hyejin; Varsaneux, Olivia; Worthington, James; Basta, Nicole E.; MacDonald, Shannon E.; Lebouché, Bertrand; Cox, Joseph; Ismail, Shainoor J.; Kronfli, Nadine
Highlights: A lack of trust in vaccine safety was a key barrier to vaccine acceptability. A lack of information was an important barrier to vaccine acceptability. Individual and collective protection were key facilitators to vaccine acceptability. Educational interventions may increase vaccination rates among incarcerated people. Trusted individuals, such as health care providers, should deliver education. Abstract: Introduction: Canadian correctional institutions have been prioritized for COVID-19 vaccination given the multiple outbreaks that have occurred since the start of the pandemic. Given historically low vaccine uptake, we aimed to explore barriers and facilitators to COVID-19 vaccination acceptability among people incarcerated in federal prisons. Methods: Three federal prisons in Quebec, Ontario, and British Columbia (Canada) were chosen based on previously low influenza vaccine uptake among those incarcerated. Using a qualitative design, semi-structured interviews were conducted with a diverse sample (gender, age, and ethnicity) of incarcerated people. An inductive-deductive analysis of audio-recorded interview transcripts was conducted to identify and categorize barriers and facilitators within the Theoretical Domains Framework (TDF). Results: From March 22–29, 2021, a total of 15 participants (n = 5 per site; n = 5 women; median age = 43 years) were interviewed, including five First Nations people and six people from other minority groups. Eleven (73%) expressed a desire to receive a COVID-19 vaccine, including two who previously refused influenza vaccination. We identified five thematic barriers across three TDF domains: social influences (receiving strict recommendations, believing in conspiracies to harm), beliefs about consequences (believing that infection control measures will not be fully lifted, concerns with vaccine-related side effects), and knowledge (lack of vaccine-specific information), and eight thematic facilitators across five TDF domains: environmental context and resources (perceiving correctional employees as sources of outbreaks, perceiving challenges to prevention measures), social influences (receiving recommendations from trusted individuals), beliefs about consequences (seeking individual and collective protection, believing in a collective "return to normal", believing in individual privileges), knowledge (reassurance about vaccine outcomes), and emotions (having experienced COVID-19-related stress). Conclusions: Lack of information and misinformation were important barriers to COVID-19 vaccine acceptability among people incarcerated in Canadian federal prisons. This suggests that educational interventions, delivered by trusted health care providers, may improve COVID-19 vaccine uptake going forward.